A criterion for continuity in a parameter of solutions to generic boundary-value problems for higher-order differential systems - Mikhailets, V. A.; Murach, A. A.; Soldatov, V. (Methods of Functional Analysis and Topology, 2016)
We consider the most general class of linear boundary-value problems for ordinary differential systems, of order r≥1, whose solutions belong to the complex space C^(n+r), with 0≤ nZ. The boundary conditions can contain derivatives of order l, with r≤ l≤ n+r, of the solutions. We obtain a constructive criterion under which the solutions to these problems are continuous with respect to the parameter in the normed space C^(n+r). We also obtain a two-sided estimate for the degree of convergence of these solutions.